Patients’ lived experiences of self-injectable diabetes treatment: A phenomenological study - Frans N. Ndara; Vistolina Nuuyoma (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences, 2023)
Background: A diabetes diagnosis has significant implications and affects the individual’s health and social opportunities; it may also carry ethical and cultural consequences, especially when self-injectable treatment is involved. Therefore, it is important to understand lived experiences of patients on self-injectable diabetes treatment to establish initiatives and develop coping mechanisms that may reduce disease morbidity.